The Use of Social Network in Daily Pediatric Practice and Education: Turkish Pediatric Atelier - Erdem Gönüllü; Ahmet Soysal; İlkay Can; Ercan Tutak; Turan Tunç; İsmail Yıldız; Osman Yeşilbaş; Naci Öner; Ali Anarat; Feryal Gün Soysal; Cengiz Bayram; Mehmet Cihan Balcı; et al. (International Journal of Pediatrics)
Using social media applications in pediatric education is not outdated, and its effectiveness has not been tested yet. For this reason, we shared the first results of the Pediatric Atelier experience that we realized through telegram application. We make an online survey to investigate the needs, requirements, pleasure, and suggestions of members through a web-based questionnaire. This cross-sectional survey study was delivered only to participants who were members of the workshop via their email addresses. Online questionnaires organized using Google Forms were sent to pediatric workshop members between March and June 2019. The questionnaire consisted of questions that measured the participants’ basic demographic data, the use of the workshop, and the overall impact of the workshop on their professional behavior. While the institutions and positions of the participants were recorded, no other personal data (such as address and telephone) were collected. Among the 997 members, 417 (42%) of them answered the questionnaire. Respondents included 300 (72%) pediatrician, 21 (5%) pediatric subspeciality fellows, and 75 (18%) pediatric subspecialists. Of the 417 respondents, 217 (52%) were working in Istanbul, and 200 (48%) were working in other cities of Turkey. Among the responders, 233 (56%) were working in private hospitals or doctor offices. A total of 520 cases were consulted in 241 days of study period. Most consultations (n=309, %59) were made from the Istanbul metropolitan area, and 203 (40%) consultations were from other cities of Turkey. The most frequently consulted departments were Pediatric infectious diseases: 166 (32%), Pediatric hematology and oncology: 56 (11%), and Neonatology: 43 (8%). Of the 520 consulted cases, 44 (8%) were related to life-threatening events, and 25 of them were hospitalized in the intensive care units, and 6 of them were required surgical operations. Of the 94% of responders thought this platform was useful and 82% of them stated that the case counseling part of the atelier was the most useful part. We think that the development of technology and artificial intelligence may lead to the usage of on-line platforms or systems in clinical medical practice. Clinical Trial Registration (if any). Registry name, registration number, web link to study on registry, and data sharing statement.